Strategi dan Peluang Indonesia dalam Kerja Sama BRICS untuk Memperkuat Keamanan Ekonomi Nasional - Muslim, Muslim; Permatasari, Diah (Jurnal Keamanan Nasional, 2024)
This study aims to explore the impact of BRICS dynamics on Indonesia's economic security, focusing on economic policies, financial initiatives, and geopolitical shifts involving BRICS countries. This research evaluates the effects of economic cooperation within BRICS, the launch of a new BRICS currency, and infrastructure investments funded by the New Development Bank (NDB) on Indonesia's financial stability, trade opportunities, and domestic economic policies. The findings indicate that while there are opportunities for Indonesia to expand trade and secure financing for infrastructure projects, challenges related to the volatility of the rupiah exchange rate and the potential dependence on foreign investments remain significant concerns. On the other hand, the potential for strategic cooperation in sectors such as energy, technology, and other industries could provide positive contributions to Indonesia's economy by enhancing global competitiveness and strengthening domestic economic resilience. This study is expected to provide valuable insights for Indonesian policymakers in formulating strategies to leverage the opportunities presented by BRICS dynamics while managing the risks of an increasingly complex global economy.